Does My Opinion Count? Interpretation and Inclusion in a Community Reading Program - Bossaller, Jenny (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The goal of community reading programs is to bring people together around a common text. In an interview, Nancy Pearl, the originator of the city-wide reading programs, said that “Reading and discussing the same book seemed to me to be a perfect way to overcome our superficial differences and understand our common humanity”… L’objectif des programmes communautaires de lecture est de rassembler les gens autour d’un même texte. Dans une entrevue, Nancy Pearl, créatrice de programmes de lecture à grande échelle, déclarait que « la lecture et la discussion d’un même livre ont semblé être des manières intéressantes de surmonter nos différences superficielles et de comprendre nos aspects humains communs »…